Plasmatic and Metamorphic Movement: The Materiality of the Moving Idea. (July 2022) - Ray, Kaustubh
In this article, the author proposes that both substance and process philosophy inadequately address the 'plasmatic' and metamorphic movement (PMM) of early animation since it subverts the logic of the 'cinematographic illusion'. Cognition, which is apparently dependent on identity formation, is predicated on substance, which conforms to representational thought. PMM, which is predicated on the 'fluid' linkage of images, destabilizes substance, consequently problematizing representation by introducing conflict between speculative substance predicated on form and perceived materiality from movement. A different problem appears with process philosophy privileging continuing flux that cannot logically be based on identity formation as it resists predication. Yet, cognition is possible as process is speculative and substance is manifest. PMM, as a manifest process that dematerializes substance, ungrounds the basis of both philosophies, simultaneously highlighting their complementarity. By problematizing both, PMM is able to highlight the relational and dependently originated nature of thought.